Examination of the Influence of Alternative Fuels on Particulate Matter Properties Emitted from a Non-Proprietary Combustor - Liam D. Smith; Joseph Harper; Eliot Durand; Andrew Crayford; Mark Johnson; Hugh Coe; Paul I. Williams (Atmosphere, 2024)
The aviation sector, like most other sectors, is moving towards becoming net zero. In the medium to long term, this will mean an increase in the use of sustainable aviation fuels. Research exists on the impact of fuel composition on non-volatile particulate matter (nvPM) emissions. However, there is more sparsity when considering the impact on volatile particulate matter (vPM) emissions. Here, nine different fuels were tested using an open-source design combustor rig. An aerosol mass spectrometer (AMS) was used to examine the mass-loading and composition of vPM, with a simple linear regression algorithm used to compare relative mass spectrum similarity. The diaromatic, cycloalkane and aromatic contents of the fuels were observed to correlate with the measured total number concentration and nvPM mass concentrations, resulting in an inverse correlation with increasing hydrogen content. The impacts of fuel properties on other physical properties within the combustion process and how they might impact the particulate matter (PM) are considered for future research. Unlike previous studies, fuel had a very limited impact on the organic aerosol’s composition at the combustor exit measurement location. Using a novel combination of Positive Matrix Factorization (PMF) and high-resolution AMS analysis, new insight has been provided into the organic composition. Both the alkane organic aerosol (AlkOA) and quenched organic aerosol (QOA) factors contained CnH2n+1, CnH2n−1 and CnH2n ion series, implying alkanes and alkenes in both, and approximately 12% oxygenated species in the QOA factor. These results highlight the emerging differences in the vPM compositional data observed between combustor rigs and full engines.